Effects of Feedback on Iranian EFL Learners\' writing Development: Group Dynamic Assessment vs. Formative Assessment - Omid Mallahi; Mahboobeh Saadat (Iranian Evolutionary Educational Psychology Journal, 2020)
Approaches to assessment are distinguished mainly by the fact that whether the provision of feedback and modification of learners performance during assessment procedures is of concern or not. In fact, Dynamic Assessment (DA) attempts to integrate assessment and instruction and uses a range of mediational strategies to gain insight into the learners current abilities and to assist them in reaching their learning potentials. Non-Dynamic Assessment (NDA), on the other hand, aims at obtaining a pure and reliable measurement of the learners abilities.The present study was designed to experimentally investigate and compare the effects of feedback offered within the frameworks of Group Dynamic Assessment (G-DA) and Formative Assessment (FA) on the improvement of 34 intermediate Iranian EFL learners writing performance and their capability in transferring the acquired knowledge and skills to new and more challenging tasks. As for the intended treatments, the G-DA students benefited from a model of classroom-based DA including three stages of orientation, execution and control and the FA students received a careful and systematic sequence of instruction, assessment and feedback. The necessary data were collected from the students in-class written drafts and their performance on four non-dynamic writing tests. Results of the analyses, especially, two-way repeated measures ANOVAs, indicated the inherent superiority of the DA group in improving their writing; however, both groups of learners were equally able to transfer the acquired knowledge and skills to new and more challenging writing tasks, which can be attributed to the satisfactory level of internalization and self-regulation they have possibly achieved as a result of the interventions received. Accordingly, it was concluded that systematic feedback offered within the frameworks of these two approaches to assessment can successfully help the learners improve their writing ability.